Answer:
c(2) = -10
Step-by-step explanation:
The first equation says that the first term of the sequence is -20.
The second equation is saying that to find any term of the sequence, add 10 to the previous term.
c(2) = c(2-1) + 10
c(2) = c(1) + 10
c(2) = -20 + 10 = -10
Answer: 36
Step-by-step explanation:
Equation: 12=6+x; x^2
1. Solve for x. X=6
2. Find x^2 or 6^2= 36.
Answer:
B is the correct answer.
Step-by-step explanation:
graph attached below, with red as the parent function (f(x)=3^x) and blue as the change (f(x)=3^x-8).
Only the 3. option can be used. All other values dont fit
Answer: x=14
Explanation: the angle needs to equal the other angle, which is 63. To figure this out, we subtract 21 from 63. We get 42. 42 divided by 3 is 14. We are basically doing the equation in reverse.